(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
During the implementation of scientific research ( Contribution to the study of fishing effort yield of Artisanal fishing gears, Quantitative and Qualitative of catch composition in the marine waters of Tortus) ) during the period ( July 2012 – August 2016 ), an individual of blue-barred parrotfish Scarus ghobban Foskskål1775 was captured for the first time in the Syrian coast ,Photographied and morphological measurements were carried out and then classified using scientific taxonomic keys. Through follow-up with fishermen about the coincidence of this species previously, It was noticed that this species appeared in the catch two times before this date, where these scenes were documented in pictures. The confirmation and documentation of the presence of Scarus ghobban , indo -Pacific origin species indicates that the biodiversity of Syrian marine waters and the eastern (Levant) basin of the Mediterranean continues to change. خلال تنفيذ بحث علمي ( دراسة انتاجية جهد الصيد بوسائل الصيد الحرفي والتركيب النوعي و الكمي في المياه البحرية لمحافظة طرطوس) في الفترة (تموز -2012 آب 2016 )، تم صيد سمكة من نوع سمكة الببغاء الزرقاء لأول مرة ، تم تصويرها ، واجريت القياسات الشكلية – القياسية لها، ثم صنفت باستخدام المفاتيح التصنيفية العلمية. ومن خلال المتابعة مع الصيادين والاستفسار منهم حول مصادفتهم لهذا النوع سابقاً، لوحظ ظهور هذا النوع في حصيلة الصيد مرتين قبل هذا التاريخ، حيث كانت هاتين المشاهدتين موثقتين بالصور. إن تأكيد وتوثيق وجود هذه السمكة Scarus ghobban ذات الأصل الهندي – الهادي يشير إلى استمرار تغير التنوع الحيوي في المياه البحرية السورية، وفي الحوض الشرقي للبحر المتوسط .